On religion the revelation of god as the sublimation of religion - "Barth, Karl" (London, 2013)
Karl Barth was one of the most important theologians of the 20thCentury and, according to Pope Pius XII, the most important since Thomas Aquinas. His magnum opus, Church Dogmatics, runs to thirteen volumes and is one of the most substantial works of systematic theology ever written. On Religion presents a central chapter from Barth's masterpiece, in which he explores the phenomenon religion itself. Including a substantial introduction and commentary, this is an essential introduction to the Church Dogmatics.
Keywords: Revalation